Avaliação de um sistema de tratamento do efluente de uma lavanderia industrial utilizando reator fotoquímico - Bavaresco, Paula Maruthia (2018)
Water, besides being essential to life, is a universal solvent used in numerous industrial processes. Its high consumption in industries generates environmental discussions and concerns due to the incorrect use and disposal that cause environmental impacts and contamination of water resources. The companies that provide laundering services, besides being an important industry in the industry, use a lot of water in their processes, thus causing a significant waste disposal. In this sense, this work has as objective to study alternative systems of treatment of laundry effluents, these being the advanced oxidative processes, thus contributing to a better management of water resources. The effluent used for the study comes from a laundry that does the washing and disinfection of uniforms that are used in a company that processes food and is located in the city of Francisco Beltrão - PR. The effluent was characterized by chemical oxygen demand (COD), biochemical oxygen demand in five days (BOD5), color, pH, total solids, conductivity and surfactants. After being collected, the effluent was submitted to reactions in a two liter photochemical reactor, with an 8 watt ultraviolet (UV) lamp inserted inside a quartz tube. To evaluate the efficiency of the treatment, BOD5 and COD analyzes were performed before and after the process used to quantify the chemical and biochemical oxygen demands of the effluent. The processes analyzed using the photochemical reactor were direct photolysis, H2O2 / UV, TiO2 / UV and TiO2 / H2O2 / UV and concentrations of 1.8 g / L H2O2 and 1.0 g / L TiO2 were used in the reactions. For the tests performed only with UV light (photolysis) a BOD removal of 17.2% and 18.8% for COD was observed. In the test performed with H2O2 / UV, it obtained a lower removal corresponding to 6.3% for BOD5 and 11.5% for COD. On the other hand, the tests carried out containing only TiO2 with UV light and TiO2 together with H2O2 and UV light did not show removal of both BOD5 and COD, although there was an increase in these parameters possibly due to the formation of intermediates during the reaction.